Standardization of Hepatitis E Virus (HEV) Nucleic Acid Amplification Technique-Based Assays: an Initial Study To Evaluate a Panel of HEV Strains and Investigate Laboratory Performance - Baylis, Sally A. (American Society for Microbiology, 2011)
The performance of hepatitis E virus (HEV) RNA nucleic acid amplification (NAT)-based assays has been investigated using a panel of HEV-containing plasma samples. The panel comprised 22 HEV-positive plasma samples representing 10-fold serial dilutions of HEV genotypes 3a, 3b, 3f, and 4c obtained from blood donors. Two negative-control plasma samples were included. All samples were blinded. The plasma samples were prepared as liquid/frozen materials and distributed to participants on dry ice. Laboratories were requested to test the panel using their routine HEV assays and to score samples as either positive or negative and could optionally return data in copies/ml for HEV RNA. Twenty laboratories from 10 different countries participated in the study. Data were returned by all participating laboratories; 10 laboratories returned quantitative data. All assays except one were developed in-house using conventional or real-time reverse transcriptase PCR (RT-PCR) methodologies. There was a 100- to 1,000-fold difference in sensitivity between the majority of assays, independent of the virus strain. Although the quantitative data were limited, for the samples in the range of ∼6 to 4 log(10) copies/ml, the standard deviations of the geometric means of the samples ranged between 0.38 and 1.09. Except for one equivocal result, HEV RNA was not detected in the negative samples. The variability of assay sensitivity highlights the need for the standardization of HEV RNA NAT assays.